Digital cousins: Simultaneous optimization of one model for BMP signaling in distant relatives reveals essential core. - Li, L.; Mdluli, T.; Buzzard, G.; Umulis, D. (Computational and structural biotechnology journal, 2025)
Spatially distributed, nonuniform morphogen gradients play a crucial role in tissue organization during development across the animal kingdom. The Bone Morphogenetic Protein (BMP) pathway, a well-studied morphogen involved in dorsal-ventral (D-V) axis patterning, has been extensively studied in zebrafish, Drosophila, and other organisms. Given that this pathway is highly conserved in both form and function, we sought to determine whether a core mathematical model that constrained topology and biophysical parameters could fully reproduce the observed dynamics of gradient formation in both Drosophila and zebrafish through changes in expression only. We used multi-objective optimization to simultaneously fit a single core model to Drosophila and zebrafish data and conditions. By exploring a single model with varied parameters, we identified both the homology and diversification of the BMP pathway. We find that variation in a small subset of parameters-particularly diffusion-related rates-can reconcile the experimentally measured BMP gradients in both species under wild-type conditions, whereas fitting both WT and mutant conditions requires additional species-specific regulatory extensions beyond the core model. This approach, involving simulation and multispecies optimization, provides a systematic method to explore the minimal parametric variations needed to account for interspecies differences in a developmental pathway. Rather than making predictive claims, our finding offers a framework for improving the interpretability and translational relevance of cross-species models.